Comparing local governance : trends and developments - Denters, S. A. H. (editor); Rose, Lawrence E. (editor) (Government beyond the centre, 2005)
This is a broad-ranging assessment of continuities and change in local governance in the western industrialised world providing in-depth assessments by leading experts of a wide range of countries exemplifying between them the whole spectrum of types and models of local government systems and networks